Examination of the Reliability and Validity of the Family Support Measurement Scale Based on Child Development Support Guidelines:Targeting Staff at Child Development Support Centers - KIMURA, Masao (Japanese Journal of Child and Family Welfare, 2024)
The purpose of this study was to develop a “Family Support Measurement Scale based on the Child Development Support Guidelines” for family support provided at child development support centers and to examine the current state of support provision through comparisons of staff attributes such as gender, age, years of experience, and job type. The results of the survey, using 156 data samples, showed that the “Family Support Measurement Scale,” based on an inductive hypothesis derived from the factor structure obtained through exploratory factor analysis and confirmed through confirmatory factor analysis using the hypothetico-deductive method, is composed of two factors: “Collaborative Approach with Parents” and “Support Focused on the Child-Rearing Environment,” as indicated by a two-factor oblique model. The goodness of fit was supported by results showing CFI = .911 and RMSEA = .090, indicating a good fit for this model. The inter-factor correlation was r = 0.698. The relevance of this scale to family social work was also considered. In the comparison of family support attributes, it was shown that staff with 7 to 9 years of experience had a higher recognition of collaborative support with parents compared to staff with less than 3 years of experience.